2015
DOI: 10.1002/cam4.553
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of growth inhibition of primary prostate epithelial cells following gamma irradiation or photodynamic therapy include senescence, necrosis, and autophagy, but not apoptosis

Abstract: In comparison to more differentiated cells, prostate cancer stem‐like cells are radioresistant, which could explain radio‐recurrent prostate cancer. Improvement of radiotherapeutic efficacy may therefore require combination therapy. We have investigated the consequences of treating primary prostate epithelial cells with gamma irradiation and photodynamic therapy (PDT), both of which act through production of reactive oxygen species (ROS). Primary prostate epithelial cells were cultured from patient samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…An increased uptake and localisation of the "capped" porphyrin could potentially explain this increased sensitivity. However DNA damage in the prostate cells (suggesting localisation occurred in the nucleus) was induced after 1 hour incubation with the porphyrin [40]. This movement into the cell and localisation of the "capped" control porphyrin is unlike-ly to have occurred in the A2780 cells in the relatively short incubation of 5 min used in this study.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…An increased uptake and localisation of the "capped" porphyrin could potentially explain this increased sensitivity. However DNA damage in the prostate cells (suggesting localisation occurred in the nucleus) was induced after 1 hour incubation with the porphyrin [40]. This movement into the cell and localisation of the "capped" control porphyrin is unlike-ly to have occurred in the A2780 cells in the relatively short incubation of 5 min used in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In a recent study [40] this "capped" control porphyrin was used in PDT experiments against benign and malignant prostate cells to assess its cytotoxic potential. "Capped" porphyrin N8.75 μM was seen to induce necrosis and prevent colony forming in irradiated prostate cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was a significant reduction in viability with the combination treatment in normal and cancer cells, however the cancer cells showed less of a reduction in viability. We have previously shown that radiation can cause senescence of primary prostate epithelial cells rather than cell death, and so the small reduction in viability as measured by alamar blue could be because the cells are senescing rather than dying [20] . Therefore, we tested the effect of three drug doses with and without 2 Gy of radiation on colony formation [ Figure 2F].…”
Section: Resultsmentioning
confidence: 99%